ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE TRADISIONAL DAN ACTIVITY BASED COSTING (ABC) PADA UD. CELLA CAKE DAN BAKERY MANADO - Kamasih, Jimmy; Saerang, David. P. E.; Mawikere, Lidya (Universitas Sam Ratulangi, 2015)
Activity Based Costing System can provide information for the better of cost calculation and can assist management to manage the company efficiently and gain a better understanding on competitive advantages, strengths, and weaknesses of the company. So that with Activity Based Costing can present carefully the information of cost product and accurately to the interests of management and comparing the cost calculation of production by using traditional methods and Activity Based Costing (ABC) at UD. Cella Cake and Bakery Manado. The purpose of this study was to determine the cost calculation of production using traditional methods and Activity Based Costing (ABC). The research method used is descriptive method. The results showed that the cost calculation of production using Activity-Based Costing System provides results that are more expensive than traditional systems on Pizza Chicken Bread, Sausage Bread and donuts. Traditional systems provide greater profit than the Activity-Based Costing system, because the calculations with the traditional system using only one cost driver so make inefficiency costs and generate profit and irrelevant